Дискусійні аспекти сучасної вітчизняної доктрини речового права - Сербенюк, С. О.; Serbenyuk, S. O. (Право і безпека. - 2024. - № 1 (92). - С. 173-185, 2024)
У статті розглянуто базисні дискусійні аспекти сучасного речового права в поєднанні з оглядом змісту українського законодавства та виокремлено основні ідеї вітчизняних учених-цивілістів щодо окремих дискусійних питань. Вони полягають у виокремленні дискусійних складових у спектрі досліджень у галузі вітчизняного речового права, оцінці подальших ефективних напрямів наукових пошуків та огляді основних положень цивільного законодавства щодо речових прав. Висвітлено основні наукові погляди і суперечності, а також точки зору законодавця щодо поняття й ознак речового права; здійснено огляд точок зору розуміння підстав виникнення речових прав та їх узагальнення і систематизацію в контексті чинного законодавства; продемонстровано проблематику класифікації об’єктів речових прав; розглянуто проблему класифікації речових прав; здійснено огляд змісту базових юридичних категорій, пов’язаних із терміном «захист речових прав», і стисло висвітлено підходи щодо класифікації способів та форм захисту речових прав.

The article examines the basic controversial aspects of modern property law in the context of an overview of the Ukrainian legislation and highlights the main ideas of national civil law scholars on certain controversial issues. They consist in identifying the debatable components in the spectrum of research in the field of national property law, assessing further effective areas of scientific research and reviewing the main provisions of civil law on property rights. The author presents the main scientific views and contradictions, as well as the legislator’s views on the concept and features of real rights; reviews the points of view of understanding the grounds for the emergence of real rights and their generalisation and systematisation in the context of current legislation; demonstrates the problems of classification of objects of real rights; considers the problem of classification of real rights; reviews the content of basic legal categories related to the term “protection of real rights” and briefly highlights the approaches to classification of methods and forms of protection of real rights. It is noted that in general, the issues of property law of Ukraine are well studied, and only some issues need to be investigated in the context of detailing already known studies or solving specific practical legal problems, in particular, legal conflicts and selection of effective methods and forms of property rights protection in a particular case under a particular set of factors or parameters. The main core of the discussions on property law is whether the notion of “thing” belongs to a particular concept and whether a wide range of property relations exists in modern social, economic and legal relations. Therefore, first of all, there are discussions about the need to enshrine in the legislation a clear definition of the content of the category “real right”, to create a detailed classification of both real rights and their objects, as well as to select an effective remedy for violated rights in accordance with the existing parameters (components) of the legal situation, etc.

В статье рассмотрены базисные дискуссионные аспекты современного вещного права в сочетании с обзором содержания украинского законодательства и выделены основные идеи отечественных ученых-цивилистов по отдельным дискуссионным вопросам.
Controversial aspects of the modern national doctrine of property law
Keywords: речове право; види речових прав; набуття речового права; захист речових прав; погляди вчених; сучасна цивілістична доктрина; property law; types of property rights; property rights acquisition; property rights protection; views of scientists; modern civil law doctrine; вещное право; виды вещных прав; приобретение вещного права; защита вещных прав; взгляды ученых; современная цивилистическая доктрина